2019
DOI: 10.1177/2158244019853908
|View full text |Cite
|
Sign up to set email alerts
|

Security Controls for Employees’ Satisfaction: Perspective of Controls Framework

Abstract: As previous literature on the effect of controls usage on the outcome of controls (controls effectiveness) are rare, this study intends to use controls framework to explain controls effectiveness as HIS (hotel information system) quality and user satisfaction. The purpose of our study is understanding of the critical role of security controls on qualities perceived by hotel employees and the satisfaction of hotel employees using HIS based on controls framework perspective. The research model was tested using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…AS practices are related to the intensification of information governance activities in these organisations that allow control of business information and enable greater analysis for strategic business purposes. These results are in line with previous studies that suggested effective InfoSec governance, policies and procedures as factors that foster short-term efficiency and greater responsiveness to the evolving needs of a business (Tallon, 2008;Lee et al, 2019). The results have also provided empirical evidence pertaining to the relationships of both constructs of AS and organisational agility in Malaysia's context.…”
Section: Discussionsupporting
confidence: 89%
“…AS practices are related to the intensification of information governance activities in these organisations that allow control of business information and enable greater analysis for strategic business purposes. These results are in line with previous studies that suggested effective InfoSec governance, policies and procedures as factors that foster short-term efficiency and greater responsiveness to the evolving needs of a business (Tallon, 2008;Lee et al, 2019). The results have also provided empirical evidence pertaining to the relationships of both constructs of AS and organisational agility in Malaysia's context.…”
Section: Discussionsupporting
confidence: 89%
“…Using social media such as Instagram and others is considered by the trends of the times and effectively targets the intended public. However, it is necessary to pay attention to the security and legal aspects of various means of communication so that the information is transparent, correct, and accountable (Fatkhudin, 2019;Aryee, 2020;Lee et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, the tendency toward these consequences is really an empirical question. Furthermore, data from social psychology studies supports the concept that diversity leads to more moderate decisions (Kong et al, 2022;Lee et al, 2019). Still, little systematic evidence of these effects on corporate board functioning exists.…”
Section: Introductionmentioning
confidence: 99%